Laparoscopic Treatment of Type III Mirizzi Syndrome by T-Tube Drainage - Yetisir, Fahri; Sarer, Akgun Ebru; Acar, H. Zafer; Polat, Yilmaz; Osmanoglu, Gokhan; Aygar, Muhittin; Parlak, Omer (Hindawi Ltd, 2016)
Mirizzi syndrome (MS) is an impacted stone in the cystic duct or Hartmann's pouch that mechanically obstructs the common bile duct. We would like to report laparoscopic treatment of type III MS. A 75-year-old man was admitted with the complaint of abdominal pain and jaundice. The patient was accepted as MS type III according to radiological imaging and intraoperative view. Laparoscopic subtotal cholecystectomy, extraction of impacted stone by opening anterior surface of dilated cystic duct and choledochus, and repair of this opening by using the remaining part of gallbladder over the T-tube drainage were performed in a patient with type III MS. Application of reinforcement suture over stump was done in light of the checking with oliclinomel N4 injection trough the T-tube. At the 18-month follow-up, he was symptom-free with normal liver function tests.
Keywords: Subtotal Cholecystectomy; Fistula; Management